An Analysis of Hyperbole in Drama "Romeo and Juliet" by William Shakespeare - Filomena Bian; I Gusti Agung Sri Rwa Jayantini; I Wayan Sidha Karya (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Language is a medium that can build human relationships with one another or the media to communicate. This research concerns to analyze hyperbole found in drama entitled “Romeo and Juliet by William Shakespeare. In this study, the researcher focuses on the total of hyperbole and the meaning of hyperbole in drama “Romeo and Juliet” by William Shakespeare. The researcher used the theory by Knickerbocker & Reninger (1963:367) to analyze the total of hyperbole and used theory by Leech (1981) to analyze the meaning of hyperbole found in drama “Romeo and Juliet” by William Shakespeare. The steps in collecting the data in this study are by found, reading, understanding, taking note and classifying the drama script are contain of hyperbole. In this study, the researcher applied descriptive qualitative method. The total of hyperbole found in drama script “Romeo and Juliet” by William Shakespeare was 8 data and three meaning found were conceptual meaning with 1 data and 12.5% of percentage, connotative meaning with 6 data and 75% of percentage and affective meaning with 1 data and 12.5% of percentage. The highest occurrence meaning of hyperbole in this drama script is connotative meaning with 6 data (75%).